Canine thyroid carcinoma prognosis following the utilisation of computed tomography assisted staging. (7th February 2021) - Giannasi, Chiara; Rushton, Steven; Rook, Alice; Steen, Nele Van Den; Venier, Francesca; Ward, Patricia (Trish); Bell, Rory; Trevail, Tim; Lamb, Valerie; Eiras, Aldara; Ellis, Jenny; Roberts, Emma
Abstract: Background: Metastatic disease is frequently present at the time of diagnosis of canine thyroid carcinoma; however, utilisation of computed tomography (CT) alone for staging pre‐treatment has been rarely reported in the veterinary literature. Methods: The aims of this retrospective study were to stage affected dogs using CT findings of the cervical and thoracic regions, combined with histopathology/cytology results, in order to assess whether metastatic disease/WHO staging was of prognostic significance. Results: Fifty‐eight dogs were included in the study. Classification of cases into WHO stages I, II, III and IV were 10%, 50%, 9% and 31%, respectively. No statistically significant effect of WHO stage classification on overall survival/follow‐up time was found ( P = .576). Surgery resulted in a statistically significant increase in overall survival/follow‐up time ( P < .01). There was no statistically significant effect on overall survival/follow‐up time in dogs that received medical therapy, either as sole therapy or as an adjunctive post‐surgery ( P = .198). Conclusion: In summary, this study documents the metastatic rate of canine thyroid carcinoma using CT for staging pre‐treatment. Staging utilising CT revealed a higher distant metastatic rate in dogs with thyroid carcinoma when compared to historical studies using different imaging techniques. As long‐term outcomes are possible for cases with advanced disease, surgical intervention could still be considered.